Residents' perspective of quality improvement and patient safety education in Canadian emergency medicine residency programs. Issue 2 (March 2020) - Trivedi, Sachin V.; Hartmann, Riley J.; Hall, Justin N.; Nasser, Laila; Porplycia, Danielle; Kwok, Edmund S. H.; Chartier, Lucas B.
ABSTRACT: Objectives: Quality improvement and patient safety (QIPS) competencies are increasingly important in emergency medicine (EM) and are now included in the CanMEDS framework. We conducted a survey aimed at determining the Canadian EM residents' perspectives on the level of QIPS education and support available to them. Methods: An electronic survey was distributed to all Canadian EM residents from the Royal College and Family Medicine training streams. The survey consisted of multiple-choice, Likert, and free-text entry questions aimed at understanding familiarity with QIPS, local opportunities for QIPS projects and mentorship, and the desire for further QIPS education and involvement. Results: Of 535 EM residents, 189 (35.3%) completed the survey, representing all 17 medical schools; 77.2% of respondents were from the Royal College stream; 17.5% of respondents reported that QIPS methodologies were formally taught in their residency program; 54.7% of respondents reported being "somewhat" or "very" familiar with QIPS; 47.2% and 51.5% of respondents reported either "not knowing" or "not having readily available" opportunities for QIPS projects and QIPS mentorship, respectively; 66.9% of respondents indicated a desire for increased QIPS teaching; and 70.4% were interested in becoming involved with QIPS training and initiatives. Conclusions: Many Canadian EM residents perceive a lack of QIPS educational opportunities and support in their local setting. They are interested in receiving more QIPS education, as well as project and mentorship opportunities. Supporting residents with a robust QIPS educational and mentorship framework may build a cohort of providers who can enhance the local delivery of care.